The Dilemma of the Presumptuous Watchdog: Constitutional Identity in the Jurisprudence of the German Federal Constitutional Court - Graser, Alex (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This article deals with the jurisprudence of the German Federal Constitutional Court relating to European integration. It provides a condensed account of this jurisprudence, from its beginnings half a century ago, to the present; it also sets out the doctrinal standards as developed by the court, and explains their interaction with both their textual bases in the German Basic Law and the procedural law of constitutional  review. The main analytical ambition of the article is to make sense of this development, and it tries to do so by reference to the court’s – changing and presumably fading – role as a central actor in shaping European integration.Keywords: German Federal Constitutional Court, European integration, democracy, rule of law, judicial governance